Peculiarities of services - a critical reflection - Carl B. Welker (IUBH Internationale Hochschule, 2020)
It has often been claimed that services are so much special and featured by challenging characteristics such as "intangibility", "perishability" "simultaneity" and "heterogeneity". This paper will show that indeed services and industrial manufacturing are both featured by same process characteristics and challenges. For this purpose, the paper introduces into the General Process Model as a tool for analysis and visualisation. Then, the named characteristics will be examined, including numerous examples easy to understand. The reader will understand that the above mentioned features either apply to any industrial manufacturing as well, or have academic but no practical relevance, or even reflect analytical failure in service theory. More important, the author points at the real issues worth being discussed: Products (services) that are highly customer-specific and demand arrivals with low predictability, both challenging capacity management and both calling for solutions manufacturing and services industries can deliver to each other.
Keywords: B40; D24; L60; L80; M10; M11; 650; service characteristics; general process model; business process reengineering; service definition; service concept; service theory